Zooplankton of the transboundary Neman River during the construction and conservation of the Baltic NPP - Dmitriy V. Kulakov (Водное хозяйство России: проблемы, технологии, управление)
Studies of the background state of the Neman River zooplankton (prior od commission of the Baltic Nuclear Power Plant) will enable to use the obtained data for assessment of the possible changes in the water fl ow and to develop measures aimed at mitigation and compensation of the damage to aquatic bio/resources.